ANALYSIS OF HOUSEHOLD CONSUMPTION OF CHICKEN IN IDO LOCAL GOVERNMENT AREA, OYO STATE - Sanusi, M M; Ashaolu, O F; Ogundipe, J B (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
This study examined household consumption of chicken in Ido Local Government Area, Oyo State. Simple random sampling technique was used to select 110 households. Data on household expenditure, socio-economic factors and other household characteristics were collected with a pre-tested questionnaire and were analyzed using descriptive statistics and tobit model. Results showed that 33.6% of the respondents preferred imported chicken because of its availability (70.9%) and ease of processing (49.1%); while 29.1% preferred domestic chicken because of its availability (20.9%) and ease of processing (49.1%). Also, 25.5% and 10.9% of the respondents spent between N1,000.00 – 1,999.90 on imported and domestic chicken, respectively per week. Only 10.0% of the respondents spent above N4,000.00 on imported chicken while none spent above N3,999.90 on domestic chicken. The tobit result revealed that education level of household-head (p<0.05), price of beef (p<0.01), non-food expenditure (p<0.05), food expenditure (p<0.05) and chicken type (P<0.01) were factors influencing consumption of chicken in the study area. In conclusion, the study found out that most households prefer imported chicken to domestic chicken due to availability in the market and ease of processing. Thus, it is recommended that stakeholders and government should encourage poultry farmers through provision of incentive and formulation of policies that will help to boost production of domestic chicken and make it more available at all times. Also, education on poultry production should be intensified so that people will be fully aware of its nutritional importance, particularly proteinous ones like chicken.